PT. Krakatau Steel (Persero) Tbk. Value Improvement through Financial Statement Benchmarking - Basuki, Bambang Tri; Sukarno, Subiakto (The Indonesian Journal of Business Administration, 2014)
Abstract-- From January 2011 to December 2012, KRAS price was continuously declining 46,22%.  On the same period, JCI was increased by 15,81%. To look into KRAS performance, benchmarking method was used to look into financial reports and financial ratios. The figures being benchmarked are Current Ratio, ROE by DuPont Method, Altman Z-Score and Sustainable Growth Rate (SGR). The Benchmarking between KRAS, 8 other publicly IDX’s iron and steel companies and the best global player POSCO are done using average and aggregate methods. The problem faced by KRAS are ROE amounted -2.67% Current Ratio 1,12.  KRAS‘s Altman Z-score 1.49 was on the DistressZone. KRAS’s SGR decline to -4.85 %. There are five objectives in formulating the alternative business solution.  Firstly, is to increase Current Ratio higher than 1.20.  Secondly, is to increase ROE above 0.0% Thirdly is to increase Altman Z-score to be higher than 1.81. Fourth is to increase SGR to be higher than 0% Lastly is to give a positive signal to investors and market players. Compiled from 6 alternatives, alternative 6 is selected because meet all the objectives of the business solution. Keywords: Current Ratio, ROE, Altman Z-Score, SGR, Aggregate